Nilai Islam dalam Budaya Masyarakat Majmuk Melalui Siri Animasi Upin dan Ipin: Islamic Cultural Values in Plural Society Through Upin And Ipin Animation Series - SIREN, NORRODZOH @ NOR RAUDAH HJ; Abdullah, Siti Aisyah Yap; Mansor, Nurul Husna (Jurnal Usuluddin, 2022)
Islamic values ​​in culture show the height and thinking of the community in carrying out the journey of life in a diverse group of races and religions. Based on the Qur’an and Sunnah as the main reference, it has explained some Islamic values ​​that need to be followed, namely basic values ​​(creed), core values ​​(Shariah) and main values ​​(morality) and delivery that is appropriate to the state of society as an additional value or development in cultural value education. Therefore, this article aims to analyse the values ​​of Islam in the culture found in those values. While the methodology for this qualitative study is to use library research and data content analysis from animated films watched. The results of the study found that the animated series Upin and Ipin have all four of those values ​​in the culture of a pluralistic society without having to separate Islamic beliefs in life together with non-Muslim societies. The content of the animated film also shows the harmonious reality of life and mutual respect among races and religions as indicated in the documentation of the Malaysian constitution.